TRPV channel-mediated calcium transients in nociceptor neurons are dispensable for avoidance behaviour - Lindy, Amanda S.; Parekh, Puja K.; Zhu, Richard; Kanju, Patrick; Chintapalli, Sree V.; Tsvilovskyy, Volodymyr; Patterson, Randen L.; Anishkin, Andriy; Rossum, Damian B.; Liedtke, Wolfgang B. van (Nature Communications, 2014)
Animals need to sense and react to potentially dangerous environments. TRP ion channels participate in nociception, presumably via Ca2+ influx, in most animal species. However, the relationship between ion permeation and animals’ nocifensive behaviour is unknown. Here we use an invertebrate animal model with relevance for mammalian pain. We analyse the putative selectivity filter of OSM-9, a TRPV channel, in osmotic avoidance behaviour of Caenorhabditis elegans. Using mutagenized OSM-9 expressed in the head nociceptor neuron, ASH, we study nocifensive behaviour and Ca2+ influx. Within the selectivity filter, M601-F609, Y604G strongly reduces avoidance behaviour and eliminates Ca2+ transients. Y604F also abolishes Ca2+ transients in ASH, while sustaining avoidance behaviour, yet it disrupts behavioral plasticity. Homology modelling of the OSM-9 pore suggests that Y604 may assume a scaffolding role. Thus, aromatic residues in the OSM-9 selectivity filter are critical for pain behaviour and ion permeation. These findings have relevance for understanding evolutionary roots of mammalian nociception.
Gesehen am 04.09.2020